Transformers, dark of the moon [videorecording (DVD)] - Bay, Michael, 1964-; LaBeouf, Shia, 1986-; Duhamel, Josh, 1972-; Turturro, John, 1957-; Tyrese; Huntington-Whiteley, Rosie, 1987-; Dempsey, Patrick, 1966-; Dunn, Kevin, 1956-; Malkovich, John; McDormand, Frances (Paramount Home Entertainment, 2011)
The Autobots learn of a Cybertronian spacecraft hidden on the moon and race against the Decepticons to reach it and to learn its secrets.